The clinical significance of p21WAF1/CIP1 protein expression in non-small cell lung cancer - Dworakowska, Dorota (Contemporary Oncology/Współczesna Onkologia, 2006)
Non-small cell lung cancer (NSCLC) is the most common human malignancy in the majority of the developed countries. Prognosis in this tumor has virtually not changed during the last decades and still remains particularly gloomy. Due to heterogeneity of NSCLC, its clinical course and biological behavior are difficult to predict reliably in an individual patient. Tumor suppressor gene WAF1/CIP1 (WAF1, Cip1, sdi1, CAP20) localized on chromosome 6p21.2, codes 21 kDa protein. The product of this gene – p21 WAF1/CIP1 protein, is activated by wild-type p53 protein and is involved in cell cycle arrest between G1/S cell cycle phases. Alteration in p21 WAF1/CIP1 protein concentration seems to be very important in cancer transformation. Because of involvement in apoptosis inhibition, WAF1/CIP1 is supposed to play a role not only as a tumor suppressor but also as a proto-oncogene. Expression of p21 WAF1/CIP1 was assessed in many non-small cell lung cancer series, however, between these papers, only a few concerned its prognostic value. In this paper the clinical significance of p21 WAF1/CIP1 in NSCLC was summarized.